Spread-out antiproton beams deliver poor physical dose distributions for radiation therapy - Paganetti, Harald; Goitein, Michael; Parodi, Katia (Radiotherapy and oncology, 2010)
Background and purpose - Antiprotons have been suggested as a possibly superior modality for radiotherapy, due to the energy released when they annihilate, which enhances the Bragg peak and introduces a high-LET component to the dose. Previous studies have focused on small-diameter near-monoenergetic antiproton beams. The goal of this work was to study more clinically relevant beams. - Methods - We used Monte Carlo techniques to simulate 120 and 200MeV beams of both antiprotons and protons of 1×1 and 10×10cm2 areas, impinging on water. - Results - An annihilating antiproton loses little energy locally; most goes into long-range secondary particles. When clinically typical field sizes are considered, these particles create a substantial dose halo around the primary field and degrade its lateral fall-off. Spreading the dose in depth further intensifies these effects. - Conclusions - The physical dose distributions of spread-out antiproton beams of clinically relevant size (e.g. 10×10cm2 area) are substantially inferior to those of proton beams, exhibiting a dose halo and broadened penumbra. Studies on the value of antiproton beams, taking radiobiological effectiveness into account, need to assess such realistic beams and determine whether their inferior dose distributions do not undermine the potential value of antiprotons for all but the smallest fields.